Situation Report: Bulgaria, 29 May 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Bulgaria Offers Incentives for Cocoon Production American Envoy Leaves Sofia Bulgarian Parliamentary Delegation Left for Finland Todor Zhivkov Tours Razgrad District A Third Shop in Kremikovtsi Put into Operation UNESCO Seminar in Sofia Bulgarian-Polish Friendship Anniversary Russian Patriarch Aleksey in Sofia